ANALYSIS OF CASE STUDY ON TAX DISPUTE OVER SALES DISCOUNTS ON INCOME TAX AND VAT: REVIEW OF LEGAL AND FINANCIAL IMPLICATIONS - Ariza, Fiby; Susmala, Windy Fatma; Novelira N, Nindya; Wahono, Puji; Pahala, Indra (JURNAL ILMIAH EDUNOMIKA, 2024)
This study delves into a case study on tax disputes over sales discounts on income tax and VAT, The study examines the legal and financial implications of sales discounts in the realm of e-commerce, emphasizing the importance of tax planning in navigating complexities and ensuring compliance with tax regulations. Highlighting the challenges faced by businesses in addressing tax disputes, the analysis offers valuable insights into the impact of sales discounts on income tax and VAT calculations. By exploring the legal framework and financial implications of tax disputes over sales discounts, the study provides a comprehensive overview of the complexities businesses encounter in the digital economy.